2013
DOI: 10.1017/s1368980013002036
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of three components of nutrition knowledge to socio-economic differences in food purchasing choices

Abstract: Objectives: To assess socio-economic differences in three components of nutrition knowledge, i.e. knowledge of (i) the relationship between diet and disease, (ii) the nutrient content of foods and (iii) dietary guideline recommendations; furthermore, to determine if socio-economic differences in nutrition knowledge contribute to inequalities in food purchasing choices. Design: The cross-sectional study considered household food purchasing, nutrition knowledge, socio-economic and demographic information. Househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 62 publications
(123 reference statements)
3
57
0
1
Order By: Relevance
“…However, we recognize that knowledge could play a broader role in food choice by supporting dietary intake regardless of food label use. Many studies have shown associations between nutrition knowledge and dietary behaviors (Ahmadi, Torkamani, Sohrabi, & Ghahremani, 2013; Bonaccio et al, 2013; Dickson-Spillmann & Siegrist, 2011; Drichoutis, Lazaridis, & Nayga, 2005; Fitzgerald et al, 2008; McKinnon et al, 2014; Wardle, Parmenter, & Waller, 2000; Worsley, 2002). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we recognize that knowledge could play a broader role in food choice by supporting dietary intake regardless of food label use. Many studies have shown associations between nutrition knowledge and dietary behaviors (Ahmadi, Torkamani, Sohrabi, & Ghahremani, 2013; Bonaccio et al, 2013; Dickson-Spillmann & Siegrist, 2011; Drichoutis, Lazaridis, & Nayga, 2005; Fitzgerald et al, 2008; McKinnon et al, 2014; Wardle, Parmenter, & Waller, 2000; Worsley, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Nutrition knowledge, broadly defined, refers to knowledge of concepts and processes related to nutrition and health including knowledge of diet and health, diet and disease, foods representing major sources of nutrients, and dietary guidelines and recommendations (Axelson & Brinberg, 1992; McKinnon, Giskes, & Turrell, 2014; Moorman, 1996; Parmenter & Wardle, 1999). Although some have argued that a narrower definition of nutrition knowledge may be desirable (Axelson & Brinberg, 1992; Li, Miniard, & Barone, 2000), Parmenter and Wardle (1999) suggest that a broad definition of nutrition knowledge is needed to capture the complex and wide-ranging nature of the information used to inform dietary choice.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the growing evidence of an association between greater fruit and vegetable consumption during childhood and reduced chronic diseases in adulthood [13][14][15][16], both short-and long-term implications of programs that successfully increase fruit intake among children are likely to be significant. However, public health initiatives should not only address deficits in nutrition knowledge [17,18], but also enduring challenges with regard to the access to and affordability of fresh, high-quality fruits-particularly among low-income children [6,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Ostensibly due to a perceived connection between public health and nutrition knowledge (McKinnon, Giskes, & Turrell, 2013), consumer advocates have consistently called for nutrition labels on commercially produced food products (Liu, Roberto, Liu, & Brownell, 2012;Roberto, Schwartz, & Brownell, 2009). Nutrition labeling is also widely recognized by U.S. consumers as useful for making better food choices in foodservice operations.…”
Section: Introductionmentioning
confidence: 99%